2009
DOI: 10.1038/nn.2379
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine activates the chemosensory cation channel TRPA1

Abstract: Topical application of nicotine, as used in nicotine replacement therapies, causes irritation of the mucosa and skin. This reaction has been attributed to activation of nicotinic acetylcholine receptors (nAChRs) in chemosensory neurons. In contrast with this view, we found that the chemosensory cation channel transient receptor potential A1 (TRPA1) is crucially involved in nicotine-induced irritation. We found that micromolar concentrations of nicotine activated heterologously expressed mouse and human TRPA1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
173
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 47 publications
7
173
4
Order By: Relevance
“…The channel contains 14-16 NH2 terminal ankyrin repeats (Story et al, 2003), an unusual structural feature that might be relevant to its proposed mechano-sensory role (Nagata et al, 2005). TRPA1 is activated by noxious cold (17 Ϯ 1°C) and is present on sensory neurons, primarily in subsets expressing TRPV1 (Story et al, 2003;Bandell et al, 2004;Nagata et al, 2005;Bautista et al, 2006;Karashima et al, 2009). Activation of TRPA1 represents, together with TRPM8 activity, the main mechanism underlying cold sensing (Dhaka et al, 2006;Wrigley et al, 2009).…”
Section: Trpa1mentioning
confidence: 99%
See 1 more Smart Citation
“…The channel contains 14-16 NH2 terminal ankyrin repeats (Story et al, 2003), an unusual structural feature that might be relevant to its proposed mechano-sensory role (Nagata et al, 2005). TRPA1 is activated by noxious cold (17 Ϯ 1°C) and is present on sensory neurons, primarily in subsets expressing TRPV1 (Story et al, 2003;Bandell et al, 2004;Nagata et al, 2005;Bautista et al, 2006;Karashima et al, 2009). Activation of TRPA1 represents, together with TRPM8 activity, the main mechanism underlying cold sensing (Dhaka et al, 2006;Wrigley et al, 2009).…”
Section: Trpa1mentioning
confidence: 99%
“…Activation of TRPA1 represents, together with TRPM8 activity, the main mechanism underlying cold sensing (Dhaka et al, 2006;Wrigley et al, 2009). Chemical activators of TRPA1 include isothiocyanates (the pungent compounds in mustard oil, wasabi and horseradish), methyl salicylate (in winter green oil), cinnamaldehyde (in cinnamon), allicin and diallyl disulphide (in garlic), acrolein (an irritant in exhaust fumes and teargas), nicotine, menthol and tetrahydrocannabinol (Bandell et al, 2004;Jordt et al, 2004;Macpherson et al, 2005;Bautista et al, 2006;Karashima et al, 2007;Talavera et al, 2009). For a more detailed review, see (McMahon and Wood, 2006).…”
Section: Trpa1mentioning
confidence: 99%
“…The authors of a recent study of menthol cigarettes concluded there was no consistent effect of menthol on perceived harshness and overall impact, 20 whereas a previous study indicated that menthol could either increase or decrease the perceived harshness of a cigarette depending on nicotine concentration. 8 Studies in mice 21,22 indicate that menthol can reduce the sensory irritation from constituents of cigarette smoke, including nicotine, that stimulate the pain receptor TRPA1, 23,24 which has been shown to play a role in cough. 25 However, the numerous other chemical and particulate irritants in tobacco smoke 5,26 have precluded direct measurement of the effect of menthol on the perception of nicotine irritation alone.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cold, it is also activated by various, mostly pungent and/or irritant compounds such as botanical substances like mustard oil, delta-9-tetrahydrocannabinol, eugenol, gingerol, methyl salicylate, allyl isothiocyanate, cinnamaldehyde, formalin, and nicotine [312][313][314][315]. Like TRPV1, TRPA1 is also considered as a key player of transduction of painful stimuli and a potential target of analgesic therapies [316][317][318][319].…”
Section: Trpa1mentioning
confidence: 99%